Computational Intelligence in Information Systems Proceedings of the Computational Intelligence in Information Systems Conference (CIIS 2018) - Omar, Saiful; Haji Suhaili, Wida Susanty; Phon-Amnuaisuk, Somnuk (Advances in Intelligent Systems and Computing, 2019)
XV, 236 p. 113 illus.